ICT Based Applications to Support Rural Development in India – A Review - Rani, Susmita; Kumar, Pankaj; Kumar, Sarvendra; Dar, Showkat Ahmad; Abhiman,; Prabhakar, Parmanand (International Journal of Bio-resource and Stress Management, 2024)
A brief review was done based on the literatures available and the findings from these research studies are used to evaluate its effectiveness on rural livelihood upliftment, poverty alleviation and implications for education and further research. Rural development in India is one of the most important factors for the growth of the Indian economy. Even after seventy years post-independence, India has not been able to come under “developed nation”, instead the nation is still developing. Public administration, governed by bureaucratic structures that dominated the twentieth century has failed to respond to the changing requirements of the present times. ICT plays a prominent role in strengthening societal development and helps to speed up the developmental process and can also bridge gaps between the educationally and technologically backward and forward sections of society. Various e-governance projects have attempted to improve the reach, enhance the base, minimize the processing costs, increase transparency and reduce the cycle times. For example, the introduction of computer and e-chaupal, radio farm forum, community radio, and ministry of rural development mobile apps such as shramik bandhu, janmanrega, meri sadak app, etc., are some of the initiatives by the government that have up to some extent been able to bring the rural population in contact with technologies. There are great opportunities for ICT application that help in democratic and sustainable development of rural India. This review mainly focuses on various ICT-based applications and their role in the Rural Development of India.